Continuous High-Dose (6 mg) vs. Low-Dose (3 mg) Intravitreal Ganciclovir for Cytomegalovirus Retinitis After Haploidentical Hematopoietic Stem Cell Transplantation: A Randomized Controlled Study - Chen, Wei-Bin; Long, Ze; Hou, Jing; Miao, Heng; Zhao, Ming-wei (Frontiers in Medicine, 2021)
Purpose: To evaluate the safety and efficacy of continuous high-dose (6 mg) intravitreal ganciclovir injections (IVG) for cytomegalovirus (CMV) retinitis (CMVR) after haploidentical hematopoietic stem cell transplantation (Haplo-HSCT), and to explore factors that may influence treatment procedure. Design: Prospective, randomized, single-blinded, positive-controlled, interventional, comparative study. Methods: A total of 22 CMVR patients (32 eyes) were randomized to either high-dose group (IVG 6mg weekly) or low-dose group (IVG 3mg given twice weekly for two weeks as induction phase and weekly thereafter as maintenance phase). Patients who were recorded any positive CMV DNAemia or other active CMV diseases and needed systemic anti-CMV treatment during the study period were excluded. Vision outcome, variables of treatment procedure and incidence of complication and CMVR recurrence were analyzed and compared. Logistic regression was applied to determine factors that may have impact on treatment process at baseline. Results: Compared to low-dose group, high-dose group resulted in a median of two less intravitreal injections (4 vs. 6 times, respectively, P=0.016), while rate of vision stability or improvement (81.2% vs. 87.5%) and incidence of complication (6.2% vs. 18.8%) and CMVR recurrence (12.5% vs. 6.2%) were similar (all P＞0.05). No drug-related toxicity was observed. Initial aqueous CMV-DNA load (OR: 6.872, 95% CI: 1.335 to 35.377, P=0.021) and extension of lesion (OR: 0.942, 95% CI: 0.897 to 0.991, P=0.020), but not dosing regimen (P=0.162), were predictors of treatment duration. Conclusions: Continuous high-dose regimen was well tolerated and resulted in less intravitreal injections, with similar vision outcome and safety profiles. The clinical course of CMVR after Haplo-HSCT was determined by its own nature at baseline and could not be modified by treatment protocols under consistent immune background.